Merdeka Belajar melalui Penggunaan Media Audio Visual pada Pembelajaran Menulis Teks Deskripsi - Ariyana Ariyana; Intan Sari Ramdhani; Sumiyani Sumiyani (LP4MK STKIP PGRI Lubuklinggau, 2020)
Critical thinking can manage the cognitive and emotional intelligence of students, based on this, free learning for educators and students is needed today. Especially in learning to write descriptive text through audio-visual media. Therefore, the purpose of this study is to describe the application of independent learning through the use of audio-visual media in learning to write descriptive texts. The research method used is descriptive qualitative method. The object of this research is descriptive text through audio-visual media which is taught at the seventh grade junior high school level. To collect data used documentation and observation techniques. Data analysis techniques were selected, interpreted, and concluded. Test the validity of the data using member checks and validation of Indonesian language learning experts. The results showed that 1) audio-visual media can help educators and students in writing descriptive text learning activities in implementing the independent learning policy, 2) audio-visual media used in learning to write descriptive text has an effect on increasing educational values, inviting students to think critically. , as well as providing a meaningful experience, 3) audio-visual media can make it easier to write descriptive text directly through the information obtained, and 4) audio-visual media will not be boring for students because the material for writing descriptive text conveyed is very varied.